Hereditary breast cancer next‐generation sequencing panel evaluation in the south region of Brazil: A novel BRCA2 candidate pathogenic variant is reported - Cesar Augusto B. Duarte; Carlos Alberto dosSantos; Cristine Domingues D. deOliveira; Cleverton César Spautz; Laura Masami Sumita; Sueli Massumi Nakatani (Molecular Genetics & Genomic Medicine)
Abstract Background In this article, we delineate a loosely selected cohort comprising patients with a history of early‐onset breast cancer and/or a familial occurrence of cancer. The aim of this study was to gain insights into the presence of breast cancer‐related gene variants in a population from a micro‐region in southern Brazil, specifically the Metropolitan Region of Curitiba. This area exhibits a highly genetically mixed population, mirroring the general characteristics of the Brazilian people. Methods Comprehensive next‐generation sequencing (NGS) multigene panel testing was conducted on 12 patients from the region, utilizing three different library preparation methods. Results Two pathogenic variants and one candidate pathogenic variant were identified: BRCA2 c.8878C>T, p.Gln2960Ter; CHEK2 c.1100del, p.Thr367Metfs15, and BRCA2 c.3482dup, p.Asp1161Glufs3. Conclusion BRCA2 c.3482dup, a novel candidate pathogenic variant, previously unpublished, is reported. The prevalence of pathogenic variants in this small cohort is similar to that described in the literature. All different library preparation methods were equally proficient in enabling the detection of these variants.